URBAN SUSTAINABLE DEVELOPMENT WITH EMPHASIS ON THE EMPOWERMENT OF INFORMAL SETTLEMENTS IN URBAN AREAS. THE CASE OF YAZD, IRAN - Azam SAFARABADI; Saeedeh MOAYEDFAR; Hamidreza VARESI (European Journal of Geography)
Informal settlement in Iran, like many countries of the world, is a growing phenomenon. Weakness of macro programs for low-income housing has provided the opportunity for the formation of informal settlements. These places, while saving low-income residents, leave negative effects on urban life and developments. The empowerment approach is among the approaches that instead of financial support reduces the negative effects of informal settlements emphasizing on the nature of the problem. This study with the aim of prioritizing the needs of the residents of Foroodgah district of Yazd develops and provides a good model for its organization and empowerment. The research method is descriptive – analytical and it is developmental and applied. Data were gathered through documentary and library studies as well as questionnaires and applying factor analysis, the needs of the community were prioritized and empowerment solutions were presented. Findings of the study revealed that informal settlements are a challenge for urban sustainable development in most countries of the world especially for less developed countries. The art of planning system is the recognition of these areas, minifying their ratio with defensive solutions, empowering and prioritizing demands, meeting their basic needs and performing empowering guidelines so that the problems are resolved and the urban sustainability be maintained.